The single mandibular implant study: short-term effects of the loading protocol on Oral Health-related Quality of Life - Schwindling, Franz Sebastian; Rädel, Michael; Passia, Nicole; Freitag-Wolf, Sandra; Wolfart, Stefan; Att, Wael; Mundt, Torsten; Reißmann, Daniel R.; Ismail, Fadi; von Königsmark, Valerie; Kern, Matthias (Journal of prosthodontic research, 2018)
Purpose - A single implant can be placed to retain an overdenture in the edentulous mandible. This study aimed at the development of Oral Health-related Quality of Life comparing immediate and delayed implant loading, i.e., loading after 3 months of submerged healing. - Methods - In a randomized controlled trial, 158 participants received a single mandibular implant in the midline. Quality of life was measured using the summary score of the German 49-item Oral Health Impact Profile at baseline, one month after implant placement (direct loading group) as well as one and four months after loading. - Results - Mean scores at baseline were comparable. Four months after implantation, a decrease of mean scores was recognized for both groups, indicating a significantly enhanced quality of life after treatment. When comparing the groups after both 1 and 4 months of loading, quality of life was insignificantly higher in the delayed loading group (1 month: 42.1 vs. 32.3; 4 months: 33.6 vs. 27.7). For immediate loading, an insignificant tendency to an earlier improvement was recognized (Δ1month-baseline: 9.7, compared to Δ1month-baseline: 6.4). - Conclusions - The single mandibular implant concept was associated with a positive impact on quality of life. However, no statistically significant influence of implant loading on quality of life was found.
Gesehen am 04.09.2019